Penerapan Problem-Based Learning Untuk Meningkatkan Pemahaman Siswa Tentang Makna Penderitaan, Wafat, dan Kebangkitan Yesus dalam Kehidupan Sehari-Hari di SDN 49 Kapur - Evi Sintha (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve students' understanding of the meaning of suffering, death, and the resurrection of Jesus through the implementation of the Problem-Based Learning (PBL) method in Catholic Religious Education at SDN 49 Kapur. The background of this research is based on the low level of students' understanding of the spiritual and moral values contained in the Easter event, as well as their minimal active involvement in the learning process, which remains teacher-centered. The method used in this research is Classroom Action Research (CAR) following the Kemmis and McTaggart model, consisting of two cycles. Each cycle involves planning, implementation, observation, and reflection. The research subjects were fifth-grade students of SDN 49 Kapur who participated in Catholic Religious Education. Data were collected through observations, interviews, formative tests, and students' written reflections. The research results indicate that the implementation of PBL significantly enhances students' understanding. In the first cycle, only 56.8% of students scored above the minimum competency criteria (KKM), whereas in the second cycle, this percentage increased to 87.5%. Additionally, this method improved students' active participation in discussions and reflections and helped them internalize the values of sacrifice, forgiveness, and hope in daily life.